Gut microbiota mediates the pro-pyroptosis effect of xierezhuyubuxu decoction in hepatocellular carcinoma - Zeng, Zhili; Feng, Mingxuan; He, Fan; Zhang, Enxin; Li, Xiushen; Cao, Zebiao (Frontiers in Microbiology, 2025)
IntroductionXierezhuyubuxu decoction (XRZYBXD) is prepared by adding and reducing the Dahuang Zhechong Pill, which is a traditional Chinese medicinal formula in “The Synopsis of Prescriptions of the Golden Chamber”. XRZYBXD has previously been reported to have good efficacy in treating Hepatocellular carcinoma (HCC) in clinical and basic research. However, its underlying mechanism in treating HCC has not been fully elucidated. The aim of the study is to investigate the pro-pyroptosis effect of XRZYBXD in HCC and the role of gut microbiota in this process.MethodsFirstly, we executed comprehensive analyses of XRZYBXD on pyroptosis, intestinal flora, microbial metabolites and intestinal barrier function using TUNEL, IHC, ELISA, WB, Q-PCR, 16S rRNA sequencing, and untargeted metabolomics in a H22 tumor-bearing mice model. Further, through rescue experiment of antibiotics-induced microbiota depletion and fecal microbial transplantation (FMT) experiment, the mechanism of XRZYBXD promoting pyroptosis of HCC by improving intestinal flora was verified.ResultsWe found that XRZYBXD medium and high dose significantly inhibited the growth of tumor and induced pyroptosis of hepatoma cells. They also modified intestinal ecological disorders by expansion of the abundance of beneficial bacteria (such as Akkermansia muciniphila and Parabacteroides distasonis) and reduction of the abundance of harmful bacteria (such as Barnesiella intestinihominis). Accordingly, microbiota metabolites and intestinal barrier function were also significantly improved by XRZYBXD.DiscussionFurther, elimination of gut microbiota by antibiotics weakened the efficacy of XRZYBXD, and FMT with feces from the XRZYBXD high dose group achieved similar therapeutic efficacy as XRZYBXD. In brief, XRZYBXD promote pyroptosis of hepatoma cells via adjusting intestinal dysbiosis.